Detection of a protein associated with acute hepatopancreatic necrosis disease (AHPND) in Litopenaeus vannamei under semi-intensive farming in Ecuador - Saavedra-Olivos, Katherine Yuliana (2018)
The present study aimed to detect a protein associated with acute hepatopancreatic necrosis (AHPND) by mass spectrometry, reared under semi-intensive farming in Ecuador. Sick shrimps from three farms were collected in the Bellavista area in the El Oro province. The hepatopancreas were macerated and cultured in TCBS medium and subcultured in TSA and LB broth. In the bacterial strains obtained, the proteins were extracted using a commercial kit and separated by SDS-PAGE gel migration. These were analyzed with a MALDI TOF/TOF mass spectrometer. The confirmation of the strains was performed by PCR using TUMSAT-Vp3 primers, which are specific for detecting AHPND. One of the strains had peptide sequences similar to that of the PirvpB protein causing AHPND, and was identified as belonging to Vibrio parahaemolyticus and carrying the gene coding for PirvpB. The results showed that it is possible to use MALDI TOF/TOF mass spectrometry in the detection of AHPND-associated proteins in shrimp culture.